Default Risk and Stock Returns: Evidence from Indian Corporate Sector. Issue 3 (June 2023) - Singh, Gurmeet; Singla, Ravi
Default risk is associated with the probability that a leveraged firm is not able to pay its financial obligation on time. Relationship between default risk and stock returns is very important from investor's point of view because it has important implication for risk and return trade off. Relationship between default risk and returns is debatable issue and contradictory results are found in the literature regarding the relationship between default risk and stock returns. Default risk assessment helps the investors and lenders to accurately assess the risks to which investors or lenders are exposed. There are several models which can be used to assess the probability of default. In the present study, the widely used Altman's Z -score model is used as a measure of default risk to find out the relationship between default risk and stock returns using simple linear regression analysis. It is found that Altman's Z -score can be used as a measure of default risk and results indicate the existence of positive relationship between Z -score and stock return and hence a negative relationship between default risk and stock return.